Establishing the need for library and information science graduate distance courses - Cornago, Pia Charmaine F.; Faderon, Rosalie B.; Santos, Herminia H. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
Professional and personality development of librarians could be spurred on by increasing access to educational opportunities. As one mechanism of increasing access to education, distance delivery methods for graduate courses were considered. The researcher sought to correlate demography and various characteristics of the population with profiles of the 'typical' distance learner in higher education as the basis for the need for LIS graduate distance courses. The purpose was not only to qualify the prospective students for distance learning, but also, to help define parameters for establishing the format of LIS graduate distance courses.
A survey questionnaire was used to collect data on the characteristics of the population and helped identify independent and dependent variables for the correlation of factors to the need for graduate distance courses. Descriptive statistics (tabular, graphical, and numerical summaries of data) was used to facilitate the presentation and interpretation of data. The values of Pearson's "r" for the paired variables implied that age and work experience respectively decrease intent to take graduate courses, while job requirement significantly increases the same intent.
Findings revealed that all had intended to take graduate courses at various times in their careers, if there were fewer constraints. For 40 of the population, time constraint was the primary cause of delay in taking graduate courses. Other major constraints were also related to lack of time: travel constraint (34), job commitments (31), and family commitments (22). The distribution of the population according to motivation for taking graduate courses was: professional development (81), skills acquisition (61) and job requirement (51). The lack of direct correlation between distance learning potential and intent to take graduate courses could imply that lack of skills did not limit the will for learning.
The respondents were found to be proficient with technology necessary for distance learning, had very good reading abilities and were inclined to finish their work on time. They had the necessary access and exposure to facilities for distance learning. The downside was that most respondents considered social interaction and classroom discussions "not particularly necessary". They needed to make use of help-seeking strategies (Taplin et al., 2001). Overcoming constraints through distance methods and thus , having greater access to graduate education, could lead to an increase in the need for graduate courses, as derived by Pearson's analysis. Higher academic completion was projected for the population if they could make full use of their resilience and potential abilities for distance learning.
Recommendation was made for further study on the refined design of a self-testing questionnaire for librarians who want to take LIS graduate distance courses. There was also the need to look into the development of "sociability"" and the nature of help-seeking that could apply to LIS graduate students (Taplin et al., 2001). The goal was to identify student characteristics which could help in better understanding and avoiding pitfalls of distance education (De Ture, 2004).
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library education; Distance education